Catalytic metasurfaces empowered by bound states in the continuum - Hu,H; Weber,T; Bienek,O; Wester,A; Huettenhofer,L; Sharp,ID; Maier,SA; Tittl,A; Cortes,E (ACS Nano, 2022)
Photocatalytic platforms based on ultrathin reactive materials facilitate carrier transport and extraction but are typically restricted to a narrow set of materials and spectral operating ranges due to limited absorption and poor energy-tuning possibilities. Metasurfaces, a class of 2D artificial materials based on the electromagnetic design of nanophotonic resonators, allow optical absorption engineering for a wide range of materials. Moreover, tailored resonances in nanostructured materials enable strong absorption enhancement and thus carrier multiplication. Here, we develop an ultrathin catalytic metasurface platform that leverages the combination of loss-engineered substoichiometric titanium oxide (TiO2–x) and the emerging physical concept of optical bound states in the continuum (BICs) to boost photocatalytic activity and provide broad spectral tunability. We demonstrate that our platform reaches the condition of critical light coupling in a TiO2–x BIC metasurface, thus providing a general framework for maximizing light–matter interactions in diverse photocatalytic materials. This approach can avoid the long-standing drawbacks of many naturally occurring semiconductor-based ultrathin films applied in photocatalysis, such as poor spectral tunability and limited absorption manipulation. Our results are broadly applicable to fields beyond photocatalysis, including photovoltaics and photodetectors.